Clinical Implications of Asymptomatic Plasmodium falciparum Infections in Malawi. (4th October 2017) - Buchwald, Andrea; Ismail, Miriam; Aceto, Courtney; Halbach, Alaina; Sixpence, Alick; Chimenya, Mabvuto; Damson, Millius; Sorkin, John; Seydel, Karl; Mathanga, Don; Taylor, Terrie; Laufer, Miriam K
Abstract: Background: In Malawi, asymptomatic Plasmodium falciparum infections are common and make up a substantial proportion of the infection burden. However, the implications of these infections for disease burden are unknown. We do not know if asymptomatic infections eventually progress to clinical malaria or if they persist without effective treatment. This study aims to characterize asymptomatic infections in a region with high transmission and examine the association between persistent asymptomatic infections and clinical disease. Methods: This study enrolled 120 participants, aged 1–50 years, with uncomplicated malaria (treated with artemether–lumefantrine) and followed them monthly for up to 2 years. Participants presenting with symptoms during follow-up were tested via rapid diagnostic test and treated if positive. Samples from all visits, regardless of symptoms, were tested for parasites using both microscopy and qPCR. Genotyping with msp1, msp2, and glurp was used to differentiate between new and persistent infections. Asymptomatic infections were defined as infections detected when symptoms were absent, and first detected at least 2 weeks before or after a symptomatic episode. Cox frailty models were used to estimate the association between asymptomatic infections and time between clinical malaria episodes; mixed models were used to estimate the odds of clinical symptoms comparing new to persistent infections. Results: Analysis has been completed for 1, 702 person months of follow-up time. Asymptomatic infections were detected in 23% of visits. After adjustment for age and season, carriage of asymptomatic infections, the longest of which persisted for 16 months, was associated with decreased risk of clinical malaria (HR 0.45, P < 0.001) in all ages. When asymptomatic infections preceded a clinical episode, newly acquired infections were detected at 92% of the following clinical episodes. After adjustment for age, sex, and season, clinical malaria was more likely to be due to newly acquired infections (OR 1.3, 95% CI 1.2–1.5) than to a persistent infection. Conclusion: In a high-transmission setting, asymptomatic P. falciparum infections infrequently developed into clinical disease and may be protective against clinical malaria. Disclosures: All authors: No reported disclosures.